Research on Childcare Support for Foreign Parents in Preschool Institutions - Taiki Fuchioka (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Increasing number of foreign children in Japan's preschool facilities and the complexity of the problems faced by foreign families are becoming more and more apparent. The social situation of high support needs for foreign parents and the lack of necessarily adequate childcare support for foreign parents, and the existing "Guidelines for Kindergarten Education (2018)," “Childcare Guidelines for Nursery Schools (2018). “And "Guidelines for Certified Nursery School Education and Childcare (2018)," describe childcare support that foreign parents cannot access directly. And In the field of preschool education practice, there is a lack of sufficient research accumulation and support for the actual situation.In other words, there is a need to find more specific ways to support foreign parents in preschool facilities. The survey method consisted of individual, semi-structured interviews, which were analyzed using Steps for Coding and Theorization (Ootani 2019). The results obtained are broadly classified into four perspectives and the discussion and conclusions are drawn from each perspective. In conclusion, the first point is an environment that facilitates the participation of foreign parents in the activities of preschool facilities; the second is support for the problems that foreign parents have; the third is support for the creation of materials and provision of information that concretely convey tacit knowledge of manners and etiquette. The third point is to support the creation of materials and provision of information that convey tacit knowledge of manners and manners in a concrete manner.